Leading new prospects: English teachers' perceptions of technology-mediated professional development - Gyawali, Yadu Prasad; Mehndroo, Meghna (Journal of Interdisciplinary Studies in Education, 2024)
The significance of technology-mediated professional development (PD) in rapidly evolving school education system in Nepal has grown substantially, particularly for English teachers attempting to acclimate to digital modalities of instruction and learning. English teachers' perspectives on technology-facilitated PD were investigated and assessed in this study. The information was gathered through semi-structured interviews conducted using Zoom. English Teachers’ viewpoints on the effectiveness, challenges, and prospective benefits of technology-enabled professional development were revealed in this study. The study encompasses a range of facets such as the accessibility of digital resources, the impact of technology on pedagogical approaches, and the overall enhancement of teaching capabilities. By providing best practices to enhance professional development practices, the study's findings support policymakers and professionals. Moreover, The study also investigated the impact of perceived relevance of professional development (PD) content on instructors' teaching practices, prior technology experience, and institutional support on perceptions